Witchcraft - Krentz, Jayne Ann (Severn House, 2010)
Mystery writer Kimberly Sawyer lives alone and likes it that way. But when she is threatened by a hooded figure, and a blood-red rose with a needle thrust into its heart is left on her doorstep, she knows she needs protection. So it seems like perfect timing when Napa Valley vineyard owner Darius Cavenaugh returns to Kimberly's life, offering help and a place to stay. But how did he know she needed him? Was it the deep, intuitive intimacy of a soulmate... or was it witchcraft?--Book jacket.